PERTUMBUHAN AWAL TANAMAN SENGON PADA BERBAGAI UKURAN LUBANG TANAM DAN DOSIS PUPUK KANDANG - Prijono, Agus (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2019)
One of main supplier on wood industry is Paraserianthes falcataria from private forestland. P. falcataria can be harvested at 5 years with the price of Rp 670,000.00 per cubic meter. P. falcataria has been planted in various areas, one of them in Widodomartani, Ngemplak , Sleman, Yogyakarta Province. The succes silviculture of P. falcataria if from planting to harvesting with good practice. One of supported succes planting is used deph holes and basic fertilizer. This research aims to determine the initial growth on some planting depth holes and compost dose. Planting is done with a distance of 2 x 2 m in the planting hole measuring control,long and wide with same each 30 cm, 40 cm, and 50cm . The planting hole each used 2 kg and 3 kg compost. The growth data (height and diameter) was taken in each treatment (7 treatments) and each treatment tree repeated . The data obtained were analyzed by anova and if there were significant differences in the factors , followed by the LSD test.The analysis showed that the treatment is significantly affect to the height and not to diameter growth. The growth rate of P. falacataria at 10 weeks planted is plsnt height 105,59 cm and 8,22 mm diameter. The planting holes 40cm x 40 cm x 40 cm and 2 kg compost giving optimal result. The best growth of P. falcataria treatment is planting holes 50cm x 50 cm x 50 cm and 2 kg compost with plsnt height 118,42 cm and 9,5 mm diameter at the 10 weeksage plant. Keywords : Growth, Sengon, planting hole, compost